A Comprehensive Study of Object Tracking Methods (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Object tracking is a key problem in many computer vision applications, including surveillance, automobile navigation, autonomous robot navigation, and so on. It detects fascinating moving items and tracks them from frame to frame. Its primary function is to detect and track a moving object or numerous objects in image sequences. Normally, there are three stages to video analysis: object detection, object tracking, and object reorganization. This paperprovides a brief overview of several video object tracking approaches, including point tracking, kernel tracking, and Silhouette tracking algorithms